The Effect of Job Training, Work Discipline, and Remuneration on Employee Work Effectiveness at PT. Serumpun Indah Lestari - Dhita Adriani Rangkuti; Sherin Khosasi; Jacinta Vella Juniva; Rosnialie (Universitas Pendidikan Ganesha, 2022)
This study tests and analyzes job training, discipline, and wages on work effectiveness at PT Serumpun Indah Lestari. The phenomenon of decreasing work effectiveness can be seen from the income at PT Serumpun Indah Lestari, the existing income at this time has decreased from 2017 to 2021, which is not able to achieve the expected revenue target. In the problem of training carried out by the company at this time only has training for employees who are just working. Providing wages to some employees who are still below the Medan regional minimum wage makes employees feel unfair and unworthy, affecting their performance and effectiveness. The lack of discipline from work hours to attendance can make the production process smoother and more timely. This research uses quantitative research with the nature of explanatory, descriptive research. The number in the study was 132 employees. Simple random sampling is used as a sampling method. The sample used was 99 people. Questionnaires and data analysis collect data through validity and reliability tests, classical assumption, and hypothesis tests. In partial data testing, training variables positively and significantly affect work effectiveness at PT Serumpun Indah Lestari. Discipline positively and significantly affects work effectiveness at PT Serumpun Indah Lestari. Wages positively and significantly affect work effectiveness at PT Serumpun Indah Lestari. In simultaneous data analysis testing, training, discipline, and wages variables positively and significantly influenced work effectiveness at PT Serumpun Indah Lestari.